A Comparison Between Selected Noncommunicable Disease Mortality Rates Between 2010 and 2016 Among Selected Southern African Countries. (January 2021) - Ellapen, T. J.; Barnard, M.; Strydom, G. L.; Masime, K. M.; Paul, Y.
Researchers have identified cancer, diabetes mellitus, cardiovascular, and respiratory diseases as being the principal pathologies of increased aged standardized death rates (ASDRs) among noncommunicable diseases (NCDs). The objective of this study was to compare the change in the ASDR of these principal NCDs between the years 2010 and 2016 in Botswana, Mozambique, Namibia, South Africa, and Zimbabwe. ASDR data were collected from the 2016 Global Health Estimate. Among the selected Southern African countries for both 2010 and 2016, the order of prevalence of NCDs linked to increased ASDR was cardiovascular diseases (both cardiac and stroke), cancer, diabetes mellitus, and chronic respiratory diseases. The percentage of the total number of NCDs linked to increased ASDR in relation to total deaths increased from 43.8% (in 2010) to 51.0% (in 2016) from ( p < .0001). The percentage of principal NCDs in relation to total ASDR increased from 33.0% (in 2010) to 38.2% (in 2016; p < .0001).